Single-center long-term results from the randomized phase-3 TARGIT-A trial comparing intraoperative and whole-breast radiation therapy for early breast cancer - Abo-Madyan, Yasser; Welzel, Grit; Sperk, Elena; Neumaier, Christian; Keller, Anke; Clausen, Sven; Schneider, Frank; Ehmann, Michael; Sütterlin, Marc; Wenz, Frederik (Strahlentherapie und Onkologie, 2019)
Partial breast irradiation using intraoperative radiotherapy (IORT) after breast-conserving surgery could be sufficient for a selected group of breast cancer patients. We report the results of a cohort of patients from a single center treated as part of the randomized phase-3 TARGIT-A trial.
Gesehen am 29.01.2021